Prevalence of nonalcoholic fatty liver disease and the related risk factors among healthy adults: A cross-sectional study in Chongqing, China - Kong, Lingxi; Yang, Yang; Li, Haidong; Shan, Youlan; Wang, Xin; Shan, Xuefeng (Frontiers in Public Health, 2023)
Background Epidemiological characteristics of nonalcoholic fatty liver disease (NAFLD) in Chongqing, west-central city of China, remains unclear.The objective of this study was to investigate the prevalence of NAFLD and the related risk factors among healthy adults for physical examination in Chongqing. Methods A total of 110626 subjects were enrolled in the present study. Each of the participants underwent physical examination, laboratory measurements and abdominal ultrasonography. Chi-square test was employed to compare differences in the NAFLD prevalence and logistic regression analysis was used to estimate the odds ratio for risk factors of NAFLD. Results Prevalence of NAFLD in Chongqing population was 28.5%, and prevalence in men (38.1%) was significantly higher than women(13.6%)(OR=2.44; 95% CI:2.31-2.58). NAFLD was more common in men aged 51-60 years and women over 60 years.79.1% of the obese people and 52.1% of the central obese people had NAFLD.Prevalence of NAFLD in people with hypertension and cholelithiasis were 48.9% and 38.4%,respectively.Logistic regression showed that gender, age,body max index(BMI), central obesity, hypertension, impaired fasting glucose/diabetes mellitus(DM), triglyceride(TG),low density lipoprotein cholesterol(LDL-C), high density lipoprotein cholesterol(HDL-C),hyperuricemia(HUA),alanine transarninase (ALT) and cholelithiasis were independently associated with the presence of NAFLD. Conclusions Prevalence of NAFLD among healthy adults in Chongqing was high. To improve prevention and management of NAFLD, special attention should be paid to the factors associated with presence of NAFLD,including higher BMI, higher waist circumference, higher blood glucose, hypertension, hypertriglyceridemia, hyperuricemia, cholelithiasis and elevated ALT.